Comparative Transcriptome Profiling Analysis Reveals the Adaptive Molecular Mechanism of Yellow-Green Leaf in Rosa beggeriana ‘Aurea’ - Gan, Ying; Kou, Yaping; Yan, Fei; Wang, Xiaofei; Wang, Hongqian; Song, Xiangshang; Zhang, Min; Zhao, Xin; Jia, Ruidong; Ge, Hong; Yang, Shuhua (Frontiers in Plant Science, 2022)
Rosa beggeriana ‘Aurea’ is a yellow-green leaf (yl) mutant and originated from Rosa beggeriana Schrenk by 60Co-γ irradiation, which is an important ornamental woody species. However, the molecular mechanism of the yl mutant remains unknown. Herein, comparative transcriptome profiling was performed between the yl type and normal green color type (WT) by RNA sequencing. A total of 3,372 significantly differentially expressed genes (DEGs) were identified, consisting of 1,585 upregulated genes and 1,787 downregulated genes. Genes that took part in metabolic of biological process (1,090), membrane of cellular component (728), catalytic (1,114), and binding of molecular function (840) were significantly different in transcription level. DEGs involved in chlorophyll biosynthesis, carotenoids biosynthesis, cutin, suberine, wax biosynthesis, photosynthesis, chloroplast development, photosynthesis-antenna proteins, photosystem I (PSI) and photosystem II (PSII) components, CO2 fixation, ribosomal structure, and biogenesis related genes were downregulated. Meanwhile, linoleic acid metabolism, siroheme biosynthesis, and carbon source of pigments biosynthesis through methylerythritol 4-phosphate (MEP) pathways were upregulated. Moreover, a total of 147 putative transcription factors were signification different expression, involving NAC, WRKY, bHLH, MYB and AP2/ERF, C2H2, GRAS, and bZIP family gene. Our results showed that the disturbed pigments biosynthesis result in yl color by altering the ratio of chlorophylls and carotenoids in yl mutants. The yl mutants may evoke other metabolic pathways to compensate for the photodamage caused by the insufficient structure and function of chloroplasts, such as enhanced MEP pathways and linoleic acid metabolism against oxidative stress. This research can provide a reference for the application of leaf color mutants in the future.